The genus Pictetia Uhlig from the Albian of Patagonia and Antarctica - Medina, Francisco Alberto; Riccardi, Alberto Carlos (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
Pictetia representatives from southern Patagonia and James Ross Island, Antarctica, are described. They are represented by Pictetia astieriana (d’Orbigny) and Pictetia ovalis COllignOn, the first coming from the Pictetia Zone of Antarctica (≈ Tardefurcata Zone) and the second from the Aioloceras rollerii Zone of Patagonia (≈ Mammillatum Standard Superzone) and from an unknown level of Antarctica. Fil: Medina, Francisco Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Riccardi, Alberto Carlos. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina